The impact of low-dose insulin on peripheral nerve insulin receptor signaling in streptozotocin-induced diabetic rats. - Kazuhiro Sugimoto; Masayuki Baba; Susumu Suzuki; Soroku Yagihashi (PLoS ONE, 2013)
BACKGROUND: The precise mechanisms of the neuroprotective effects of insulin in streptozotocin (STZ)-induced diabetic animals remain unknown, but altered peripheral nerve insulin receptor signaling due to insulin deficiency might be one cause. METHODOLOGY AND PRINCIPAL FINDINGS: Diabetes was induced in 10-week-old, male Wistar rats by injecting them with STZ (45 mg/kg). They were assigned to one group that received half of an insulin implant (∼1 U/day; I-group, n = 11) or another that remained untreated (U-group, n = 10) for 6 weeks. The controls were age- and sex-matched, non-diabetic Wistar rats (C-group, n = 12). Low-dose insulin did not change haemoglobin A1c, which increased by 136% in the U-group compared with the C-group. Thermal hypoalgesia and mechanical hyperalgesia developed in the U-group, but not in the I-group. Sensory and motor nerve conduction velocities decreased in the U-group, whereas sensory nerve conduction velocity increased by 7% (p = 0.0351) in the I-group compared with the U-group. Western blots showed unaltered total insulin receptor (IR), but a 31% decrease and 3.1- and 4.0-fold increases in phosphorylated IR, p44, and p42 MAPK protein levels, respectively, in sciatic nerves from the U-group compared with the C-group. Phosphorylated p44/42 MAPK protein decreased to control levels in the I-group (p<0.0001). CONCLUSIONS AND SIGNIFICANCE: Low-dose insulin deactivated p44/42 MAPK and ameliorated peripheral sensory nerve dysfunction in rats with STZ-induced diabetes. These findings support the notion that insulin deficiency per se introduces impaired insulin receptor signaling in type 1 diabetic neuropathy.